Basic Equations
The anisotropic conduction equation looks like
\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \left ( \chi_\parallel - \chi_\perp \right ) \left ( \hat{b} \cdot \nabla T \right ) + n \chi_\perp \nabla T \right ]
however, the conduction coefficients have a Temperature dependence.
\chi_\parallel = \kappa_\parallel T^{5/2}
\chi_\perp = \kappa_\perp \frac{n}{B^2 T^{1/2}}
Collecting power's of T
So we can rewrite the equations as
\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \left ( \kappa_\parallel T^{\lambda_\parallel} - \frac{n \kappa_\perp}{B^2} T^{\lambda_\perp} \right ) \left ( \hat{b} \cdot \nabla T \right ) + \frac{n \kappa_\perp}{B^2} T^{\lambda_\perp} \nabla T \right ]
or
\frac{\partial T}{\partial t} = \nabla \cdot \left [ n \hat{b} \left ( \frac{\kappa_\parallel}{\lambda_\parallel+1} \left ( \hat{b} \cdot \nabla T^{\lambda_\parallel+1} \right ) - \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp+1 \right )} \left ( \hat{b} \cdot \nabla T^{\lambda_\perp + 1} \right ) \right ) + \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp +1 \right )} \nabla T^{\lambda_\perp+1} \right ]
Einstein simplification
or in Einstein notation
\partial_t T = \partial_i \left [ n b_i \left ( \frac{\kappa_\parallel}{\lambda_\parallel+1} \left ( b_j \partial_j T^{\lambda_\parallel+1} \right ) - \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp+1 \right )} \left ( b_j \partial_j T^{\lambda_\perp + 1} \right ) \right ) + \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp +1 \right )} \partial_i T^{\lambda_\perp+1} \right ]
or
\partial_t T = \partial_i \left [ n b_i \left ( \frac{\kappa_\parallel}{\lambda_\parallel+1} \left ( b_j \partial_j T^{\lambda_\parallel+1} \right ) - \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp+1 \right )} \left ( b_j \partial_j T^{\lambda_\perp + 1} \right ) \right ) + \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp +1 \right )} \delta_{ij} \partial_j T^{\lambda_\perp+1} \right ]
or
\partial_t T = \partial_i n b_i \frac{\kappa_\parallel}{\lambda_\parallel+1} b_j \partial_j T^{\lambda_\parallel+1} + \partial_i n \left ( \delta_{ij} - b_i b_j \right ) \frac{n \kappa_\perp}{B^2 \left ( \lambda_\perp + 1\right )} \partial_j T^{\lambda_\perp+1}
or
\partial_t T = \frac{\kappa_\parallel}{\lambda_\parallel+1} \partial_i n b_i b_j \partial_j T^{\lambda_\parallel+1} + \frac{\kappa_\perp}{\left ( \lambda_\perp + 1\right )} \partial_i n^2 B^{-2} \left ( \delta_{ij} - b_i b_j \right ) \partial_j T^{\lambda_\perp +1}
Implicitization
Now we can rewrite the equation
\partial_t T = \displaystyle \sum_{\parallel, \perp} A \partial_i B_{ij} \partial_j T^{\lambda+1}
where the \parallel or \perp subscript on A, B_{ij}, and lambda is implied.
A_\parallel = \frac{\kappa_\parallel}{\lambda_\parallel + 1} and A_\perp = \frac{\kappa_\perp}{\lambda_\perp + 1}
and B_{\parallel, ij} = n b_i b_j and B_{\perp, ij} = n^2 B^-2 b_i b_j \left ( 1 - \delta_{ij} \right )
Now to solve this implicitly, we need to replace T with T_* where
T_* = T + \phi ( T' - T ) = (1-\phi) T + \phi T'
Note for Backward Euler, \phi = 1 and for Crank Nicholson, \phi = 1/2
\partial_t T = \displaystyle \sum_{\parallel, \perp} A \partial_i B_{ij} \partial_j T_*^{\lambda+1}
It is simpler to linearize the equation in terms of T_* and then subsitute then vice-versa - though both give the same answer
T_*^{\lambda + 1} \approx T^{\lambda + 1} + \left ( \lambda + 1 \right ) T^{\lambda} \left ( T_{*} - T \right ) = T^{\lambda + 1} + \left ( \lambda + 1 \right ) T^{\lambda} \phi \left ( T' - T \right )
= \left(1 - \phi \left ( \lambda + 1\right ) \right ) T^{\lambda + 1}+ \phi \left ( \lambda + 1 \right ) T^{\lambda} T'
So we have
\partial_t T = \displaystyle \sum_{\parallel, \perp}{A \partial_i B_{ij} \partial_j \left [ \left ( 1 - \phi \left ( \lambda + 1 \right ) \right )T^{\lambda + 1} + \phi \left ( \lambda + 1 \right ) T^{\lambda} T' \right ]}
\partial_t T = \displaystyle \sum_{\parallel, \perp}{A \partial_i B_{ij} \left [ \left ( 1 - \phi \left ( \lambda + 1 \right ) \right ) \partial_j T^{\lambda + 1} + \phi \left ( \lambda + 1 \right ) \partial_j T^{\lambda} T' \right ]}
\partial_t T = \displaystyle \sum_{\parallel, \perp}{A \partial_i B_{ij} \left [ C \partial_j T^{\lambda + 1} + D \partial_j T^{\lambda} T' \right ]}
where C= \left ( 1 - \phi \left ( \lambda + 1 \right ) \right ) and D = \phi \left ( \lambda + 1 \right )
Now we can expand the derivatives and get
Expand Derivatives
\partial_t T = \displaystyle \sum_{\parallel, \perp}{A \left ( \partial_i B_{ij} \right ) \left ( C \partial_j T^{\lambda + 1} + D \partial_j T^{\lambda} T' \right ) + A B_{ij} \left ( C \partial_i \partial_j T^{\lambda + 1} + D \partial_i \partial_j T^{\lambda} T' \right )}
We can also write this as
\partial_t T = \displaystyle \sum_{\parallel,\perp}{CE_j \partial_j T^{\lambda + 1} + DE_j \partial_j T^{\lambda} T' + CF_{ij} \partial_i \partial_j T^{\lambda + 1} + DF_{ij} \partial_i \partial_j T^{\lambda} T'}
where
E_j = A \left ( \partial_i B_{ij} \right )
F_{ij} = A B_{ij}
Discretization
We then need expressions for
\partial_t T = \frac{ T'_0 - T_0}{\Delta t}
\partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{j}} - T^{\lambda+1}_{-\hat{j}}}{2 \Delta x}
\partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{j}}T'_{\hat{j}} - T^{\lambda}_{-\hat{j}}T'_{-\hat{j}}}{2 \Delta x}
\partial_i\partial_j T^{\lambda+1} = \frac{T^{\lambda+1}_{\hat{i}+\hat{j}} - T^{\lambda+1}_{\hat{i}-\hat{j}}-T^{\lambda+1}_{-\hat{i}+\hat{j}} + T^{\lambda+1}_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) + \frac{T^{\lambda+1}_{\hat{i}} - 2T^{\lambda+1}_{0} + T^{\lambda+1}_{-\hat{i}}}{\Delta x^2}\delta_{ij}
\partial_i\partial_j T^{\lambda}T' = \frac{T^{\lambda}_{\hat{i}+\hat{j}}T'_{\hat{i}+\hat{j}} - T^{\lambda}_{\hat{i}-\hat{j}}T'_{\hat{i}-\hat{j}}-T^{\lambda}_{-\hat{i}+\hat{j}}T'_{-\hat{i}+\hat{j}} + T^{\lambda}_{-\hat{i}-\hat{j}}T'_{-\hat{i}-\hat{j}}}{4 \Delta x^2}\left(1-\delta_{ij}\right ) + \frac{T^{\lambda}_{\hat{i}}T'_{\hat{i}} - 2T^{\lambda}_{0}T'_{0} + T^{\lambda}_{-\hat{i}}T'_{-\hat{i}}}{\Delta x^2}\delta_{ij}
Using the above definitions, we can write the discretized equation as
T_0 - \displaystyle \sum_{\parallel, \perp} C \left [ \alpha_0 T^{\lambda+1}_0 + \displaystyle \sum_{\pm j} \alpha_{\pm j} T^{\lambda+1}_{\pm \hat{j}} + \sum_{\pm i, \pm j,i \ne j} \alpha_{\pm i, \pm j} T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}} \right ] =
T'_0 + \displaystyle \sum_{\parallel, \perp} D \left [ \alpha_0 T^{\lambda}_0T'_0 + \displaystyle \sum_{\pm j} \alpha_{\pm j} T^{\lambda}_{\pm \hat{j}} T'_{\pm \hat{j}} + \sum_{\pm i, \pm j,i \ne j} \alpha_{\pm i, \pm j} T^{\lambda}_{\pm \hat{i} \pm \hat{j}} T'_{\pm \hat{i} \pm \hat{j}} \right ]
where
\alpha_0 = -\frac{2F_{ij}\delta_{ij} \Delta t}{\Delta x^2}
\alpha_{\pm j} = \pm \frac{E_j \Delta t}{2 \Delta x} + \frac{F_{jj}\Delta t}{\Delta x^2}
\alpha_{\pm i, \pm j} = \pm \pm \frac{F_{ij}\Delta t}{4 \Delta x^2}
Summary
| \parallel | \perp
|
A | \frac{\kappa_\parallel}{\lambda_\parallel + 1} | \frac{\kappa_\perp}{\lambda_\perp + 1}
|
B_{ij} | n b_i b_j | n^2 B^-2 b_i b_j \left ( 1 - \delta_{ij} \right )
|
C | \left ( 1 - \phi \left ( \lambda_\parallel + 1 \right ) \right ) | \left ( 1 - \phi \left ( \lambda_\perp + 1 \right ) \right )
|
D | \phi \left ( \lambda_\parallel + 1 \right ) | \phi \left ( \lambda_\perp + 1 \right )
|
And then using those we can calculate
E_j | A \left ( \partial_i B_{ij} \right )
|
F_{ij} | A B_{ij}
|
\alpha_0 | -\frac{2F_{ij}\delta_{ij} \Delta t}{\Delta x^2}
|
\alpha_{\pm j} | \pm \frac{E_j \Delta t}{2 \Delta x} + \frac{F_{jj}\Delta t}{\Delta x^2}
|
\alpha_{\pm i, \pm j} | \pm \pm \frac{F_{ij}\Delta t}{4 \Delta x^2}
|